Popperian analysis of positivistic inquiry in indonesian biology education - Tegar Satya Prahara; Nur Hafizah; Slamet Suyanto (Biosfer: Jurnal Pendidikan Biologi, 2026)
This study aims to examine the epistemological tendencies underlying inquiry-based biology learning in Indonesia and to critically interpret them through Karl Popper’s falsificationism. A systematic literature review was conducted using the PRISMA procedure across Google Scholar, SINTA, ERIC, DOAJ, and Garuda databases, focusing on studies published between 2018 and 2025. Fifteen articles that met the inclusion criteria were analyzed through open coding and philosophical interpretation to identify patterns of scientific rationality in inquiry-based biology education. The findings show that inquiry is predominantly implemented in a verification-oriented and procedural manner, with success mainly measured through quantitative learning outcomes, science process skills, and scientific literacy scores. These practices reflect a positivistic orientation and provide limited opportunities for students to formulate risky conjectures, examine counter-evidence, and revise ideas through critical reflection. Based on these findings, biology education should reorient inquiry toward a reflective–critical approach that emphasizes severe testing, argumentation-based discussion, and contextual biological problem-situations so that students can develop stronger epistemic understanding and a more authentic view of scientific inquiry.